Economic Efficiency and Growth Sustainability of Indian Small Scale Industries : A Pre and Post-Liberalization Based Comparative Analysis - Bhullar, Amanat; Singh, Parminder (Arthshastra Indian Journal of Economics & Research, 2017)
Economic sustainability requires the development of an industrial sector which sequentially leads to economic development. The major thrust of the present paper was to analyze the overall economic efficiencies of the Indian small scale industrial sector. The study was confined to the period from 1980-81 to 2013-14 which was further divided in two phases, that is, pre reform period (1980-1981 to 1990-1991) and post reform period (1991-1992 to 2013-2014). For the purpose of the study, data were curled from Annual Survey of Industries (ASI) statistics prepared by Small Industrial Development Organization (SIDO) and data compiled by Planning Commission. To perform the analysis, data envelopment analysis was used and the Tobit regression model was utilized to analyze the factors effecting efficiencies. The results showed that the average overall technical efficiencies and economic efficiencies were 0.61 and 0.78, respectively. We suggested that the government should implement financial reform packages that foster competition in the banking market, and that the industry should devise incentive schemes to improve managerial efficiency.